Supramolecular gold(i) vesicles: an in-depth study of their aggregation process. Issue 23 (20th September 2022) - Pinto, Andrea; Sonet, Jaume; Gomila, Rosa M.; Frontera, Antonio; Lima, João Carlos; Rodríguez, Laura
Abstract : The synthesis and aggregation behaviour of two gold(i ) complexes containing a pyridyl ligand with a polyethyleneglycol pendant arm at one position and a chromophore (aniline or coumarin) at the second coordination position is herein reported. Abstract : The synthesis of two gold(i ) complexes containing a pyridyl ligand with a polyethyleneglycol pendant arm at one position and a chromophore (aniline or coumarin) at the second coordination position is herein reported. These compounds have been observed to aggregate in acetonitrile/water mixtures and the results have been compared with two other gold(i ) compounds previously synthesized by our group that contain a water soluble phosphane instead of the pyridyl ligand. We observed that the coumarin derivative is much more stable while the aniline analogue decomposes in the presence of small amounts of water. The aggregation of this coumarin gold(i ) compound has been deeply studied by DLS, SAXS, optical microscopy and electron microscopy (SEM and cryo-TEM). The calculation of the crystal packing parameter confirms a vesicle-type assembly. In order to obtain more detailed information about the composition of vesicles, the number of molecules involved in the self-assembly process has been determined ( N agg = 82). DFT calculations support these data, determining a size of around 90 Å for the vesicles, which may form coacervates to yield the larger structures observed under a microscope.